2017
DOI: 10.1021/acs.jpcc.6b11757
|View full text |Cite
|
Sign up to set email alerts
|

Explosion Study of Nitromethane Confined in Carbon Nanotube Nanocontainer via Reactive Molecular Dynamics

Abstract: Explosion dynamics of confined nitromethane (NM) fluid has been investigated by using nonequilibrium reactive molecular dynamics. For the confinement, NM was encapsulated into a nanocontainer, which is the capped (20, 20) armchair carbon nanotube (CNT). After thermal energy was injected into confined NM at various densities, the nanobomb consisting of NM and CNT was fully decomposed including bursting phenomena. We found that the time for explosion was reduced as density and initial temperature increased. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…A plant working upon the manufacture of TNM on an industrial scale was destroyed by an explosion in 1953 . There have been many experimental investigations on the pyrolysis and photolysis of TNM. , In addition, extensive simulations have been carried out to study the thermal or photochemical decomposition of the simplest nitroalkane, e.g., nitromethane (NM). For instance, Fileti et al reported the detonation kinetics and explosion reaction of NM computed by reactive force field (ReaxFF) molecular dynamics (MD) simulations . However, to our knowledge, theoretical studies addressing the photodissociation of TNM due to photoinduced electronic transitions are limited.…”
mentioning
confidence: 99%
“…A plant working upon the manufacture of TNM on an industrial scale was destroyed by an explosion in 1953 . There have been many experimental investigations on the pyrolysis and photolysis of TNM. , In addition, extensive simulations have been carried out to study the thermal or photochemical decomposition of the simplest nitroalkane, e.g., nitromethane (NM). For instance, Fileti et al reported the detonation kinetics and explosion reaction of NM computed by reactive force field (ReaxFF) molecular dynamics (MD) simulations . However, to our knowledge, theoretical studies addressing the photodissociation of TNM due to photoinduced electronic transitions are limited.…”
mentioning
confidence: 99%
“…For the systems subjected to high temperature, a rapid rise of the temperature was observed due to the formation of water molecules, which was the most exothermic reaction in the NM decomposition mechanism, as reported in our previous work (Figure S5c). Note that even though water molecules were produced when the system was heated at 2000 K, the highest fraction of water molecules produced was ∼0.1. At the final stage of nanobomb decomposition, the nanobomb heated to 2500 K exhibited a sudden temperature rise at around 350 ps, where the CNT container was ruptured.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we applied in silico design to a nanobomb composed of nitromethane (NM) and carbon nanotubes (CNTs) . A nanobomb is a new type of nanoenergetic material system, where a few tens to hundreds of NM molecules are confined in a nanometer-sized CNT.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, molecular and crystal structures, including chemical composition, crystal packing, crystal morphology, size, shape, purity, and defects, are strongly related to the intrinsic qualities of the materials. Until now, various strategies, such as recrystallization, energetic co-crystals, adding and coating of the inert materials including with organic wax [7], high polymers [8], stearic acid [9], and carbon materials (CMs) [10,11,12,13,14,15,16,17,18,19,20,21,22], have been proposed to reduce the sensitivity and improve the performance of EMs.…”
Section: Introductionmentioning
confidence: 99%
“…Ab initio molecular dynamics simulations by Liu et al showed that functionalized graphene with a carbon vacancy defect could greatly accelerate the thermal decomposition of nitromethane and its derivatives [21]. Moreover, using nonequilibrium reactive molecular dynamics, Lee et al studied the explosion dynamics of nitromethane confined in a carbon nanotube nanocontainer, which provided some new insights into nanoscale explosions [22].…”
Section: Introductionmentioning
confidence: 99%